2021
DOI: 10.1080/08961530.2021.1982807
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumers’ Sentiment Expressions in Online Reviews: A Hybrid Approach

Abstract: Understanding consumers' sentiment expressions in online reviews: a hybrid approachThis study explores consumers' sentiment and its influencing factors in the context of theme parks by analyzing online reviews. A hybrid approach is employed, including sentiment analysis, logistic regression analysis and cooccurrence network analysis. The findings provide new insights on the sentiment expression of consumers in different regions, that is, Australian consumers express significantly more positive sentiment than U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Moreover, as indicated in the results from "after COVID-19" dataset, XGBoost with BoW achieved the highest accuracy of 89.16%. The prediction accuracies achieved in this study can be considered superior to the results of existing studies (Hwang et al, 2020;La et al, 2021). Overall, Logistic regression with TF-IDF and XGBoost with BoW are proposed to have better performances in predicting user satisfaction for healthcare services.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Moreover, as indicated in the results from "after COVID-19" dataset, XGBoost with BoW achieved the highest accuracy of 89.16%. The prediction accuracies achieved in this study can be considered superior to the results of existing studies (Hwang et al, 2020;La et al, 2021). Overall, Logistic regression with TF-IDF and XGBoost with BoW are proposed to have better performances in predicting user satisfaction for healthcare services.…”
Section: Discussionmentioning
confidence: 63%
“…Additionally, Shah et al (2021) confirmed that random forest (accuracy: 93.17%) and logistic regression (accuracy: 90.88%) has a higher accuracy than multinomial and Bernoulli Naïve Bayes models in forecasting user satisfaction with certain products. La et al (2021) predicted tourists' satisfaction by analyzing their online comments with Logistic regression and found the classifier to have an accuracy of 80.95%. Luo et al (2021) analyzed online reviews using random forest to predict positive/negative customer ratings for restaurant services.…”
Section: User Satisfaction With Mobile Healthcare Servicesmentioning
confidence: 99%
“…Still based on the equity theory, when individuals experience strong consumption dissatisfaction, they will desire to vent their negative feelings, leading them to write more enriched reviews. Therefore, we argue that experienced travelers are inclined to post richer reviews with photos, more words and more affective content to express their emotions (Hong et al, 2016;Huang et al, 2017;La et al, 2021). We thus put forward the hypotheses as follows:…”
Section: 22mentioning
confidence: 99%
“…Lee et al [25] indicated that an algorithm combining VADER and machine learning is an effective methodology for sentiment analysis using metaverse mobile application service reviews. La et al [26] found that logistic regression is an appropriate model for analyzing the online comments of tourists. [27] used online restaurant reviews to discover the model that could predict positive or negative scores.…”
Section: Sentiment Analysis Utilizing Social Network Services Datamentioning
confidence: 99%